Synthesis of Acylated Naphthohydroquinones Through Photo-Friedel–Crafts Acylation and Evaluation of Their Antibiotic Potential - Alexis Mercier; Alizée Monet; Madyan A. Yaseen; M. Iris Hermanns; Michael Oelgemöller (Photochem)
A variety of 1-(1,4-dihydroxynaphtalen-2-yl) ketones was synthesized using the photo-Friedel–Crafts acylation of 1,4-naphthoquinone with aldehydes. Subsequent oxidation using silver oxide readily furnished the corresponding 2-acylated 1,4 naphthoquinones. Notably, these naphthoquinone derivatives underwent spontaneous partial reduction upon storage. The synthesized compounds were subjected to antimicrobial screening. High inhibition effects on Staphylococcus aureus were found for the majority of compounds, which makes them interesting for potential future medicinal applications.